MULTIFOCAL EPILEPSY – VIEW OF MODERN NEUROPHYSIOLOGIST - V. O. Generalov; G. N. Avakyan; T. R. Sadykov; Yu. V. Kazakova (Эпилепсия и пароксизмальные состояния, 2016)
Data of own examinations and literature analysis regarding multifocal epilepsy are presented in the article. The analysis of etiology, clinical implications and prognostic factors of multifocal epilepsy of children and adults was done. It was discovered that the reasons of multifocal epilepsy in children are epileptic encephalopathies, genetic canalopathies and consequences of perinatal brain lesions. Formation of multifocal epilepsy in adults is associated with traumatic, ischemic and toxic factors, etc. Localization of epileptic sources is directly associated with zone of lesion: the source is located perifocally to zone of lesion in the structure or mediobasal temporal zones, that are more sensitive to diffusive effect of lesion (toxic and ischemic). More often localization of sources of epileptic activities in children is not associated with lesion character and zone. Multifocal epilepsy in children has very unfavorable prognosis, especially if caused by current pathological process (epileptic encephalopathy, neuroinfection). And on the contrary, multifocal epilepsy in adults is more successfully treated.